Junior doctors and improving the quality of care for older people in hospital - Fisher, James (Future Hosp J, 2016)
A number of recent high-profile reports have described sub-optimal care of older people in UK hospitals. Older people already form the bulk of hospital inpatient work and it is recognised that they often experience adverse events as a result of their hospitalisation. This, coupled with an ageing population, means there is great need to improve the quality of care for older hospitalised patients. In this article, we argue that junior doctors can, and should, play a central role in the process of improving the quality of care for older people in hospital. We describe a series of innovative, trainee-led projects that have sought to improve quality of care for hospitalised older people. Lastly, we explore how senior clinicians can support junior colleagues to make meaningful, sustainable change, with specific reference to induction processes, quality-improvement projects and role modelling.